Chlorophenyl thiophene silicon phthalocyanine: Synthesis, two-photon bioimaging-guided lysosome target, and in vitro photodynamic efficacy - Xu, Le; Zhang, Tiantian; Huang, Bingcheng; Zheng, Fangmei; Huang, Yan; Li, Yuyang; Peng, Yiru; Chen, Linying (Frontiers in Pharmacology, 2023)
The development of efficient photosensitizers with high singlet oxygen quantum yield, strong fluorescent emission, excellent photostability, and specific organelle targeting is in great demand for the enhancement of PDT treatment efficiency. This study designed and synthesized a new two-photon photosensitizer chlorophenyl thiophene axially substituted silicon (IV) phthalocyanine (CBT-SiPc). CBT-SiPc showed specific targeting of lysosomes in living cells and good biocompatibility. Furthermore, high 1O2 generation efficiency and high PDT efficiency in MCF-7 breast cancers under irradiation were also demonstrated. The novel CBT-SiPc showed great potential in the application of lysosome-targeted and two-photon bioimaging-guided photodynamic cancer therapy.